Effect of impregnate nanocellulose with ethylene glycol for car radiator application - Ihsan Naiman, Ibrahim; Norazlianie, Sazali; D., Ramasamy; Ahmad Shahir, Jamaludin; Mohd Syafiq, Sharip; Haziqatulhanis, Ibrahim (Akademi Baru, 2019)
One of the efforts to increase the effectiveness of radiator is by adding nanocellulose in radiator coolant. Furthermore, the percentage of nanocellulose plays an important role to make sure that the amount of heat transfer can be increased by increasing the percentage of nanocellulose. The nanocellulose is used in this experiment as the nanoparticles. Radiator was modelled using One-Dimensional simulation software to predict the performance characteristics and effectiveness of the radiator with addition of nanoparticles. Besides that, method of using micro channels and fins to extend the cooling rate of a radiator ended up being a traditional technology which already reached to its maximum limit. Moreover, Heat transfer coefficient of cellulose nanofluids can be increased by increasing the size of the radiator. Increase in size of radiator may enhance better and help to increase the rate of heat transfer. In addition, it clearly states that when the flow rate of the coolant or working fluid in the radiator cooling system increase the rate of heat transfer also is increases.